2005
DOI: 10.1128/jvi.79.20.13007-13017.2005
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Utilization of an ATM Signaling Pathway by Polyomavirus

Abstract: Progression from G 1 to S is essential for polyomavirus DNA replication and depends on the interaction of large T with the retinoblastoma gene product pRb. This virus-induced replication pathway is accompanied by p53 activation resembling a DNA damage response (12). We sought to determine whether this pathway depends in part on activation of the ATM (ataxia telangiectasia mutated) kinase and whether the virus gains advantages from this pathway beyond that of entry into S. We show that polyomavirus infection ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
126
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 52 publications
4
126
1
Order By: Relevance
“…Thus, the MVC and MVM infection systems both provide simple models in which to study the DDR induced by the ssDNA genome of parvovirus. It is now clear that, like other DNA viruses (27,56), the autonomous parvovirus hijacks the cellular DDR machinery to facilitate replication of its genome.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the MVC and MVM infection systems both provide simple models in which to study the DDR induced by the ssDNA genome of parvovirus. It is now clear that, like other DNA viruses (27,56), the autonomous parvovirus hijacks the cellular DDR machinery to facilitate replication of its genome.…”
Section: Discussionmentioning
confidence: 99%
“…SV40 lytic infection thus triggers the DNA damage checkpoint, resulting in a bypass of mitosis and additional replication of cellular and viral DNA (9), and murine polyomavirus-infected cells accumulate in S and G 2 phases (10). Replication of viral DNA in cells infected with SV40 or murine polyomavirus has also been recently shown to activate the ataxia telangiectasia mutated (ATM)-mediated signaling pathway and thereby promote viral replication (11,12). However, it is not clear how polyomaviruses trigger DNA damage signaling.…”
mentioning
confidence: 99%
“…p53 inhibits Cdc2 through the activation of p21 cip1/waf1 and through its feedback loop to regulate ATM (Lavin and Kozlov, 2007). Activated ATM phosphorylates several downstream targets, including Brca1, Nbs1, p53, and Chk2 (Dahl et al, 2005;Lavin and Kozlov, 2007;Zhao et al, 2008), temporarily blocking the cell cycle to facilitate the repair of lesions before cell division. Recently, it is reported that p53 is regulated by MDM2, which associates with Daxx.…”
Section: Discussionmentioning
confidence: 99%